Estrés laboral percibido en profesionales y auxiliares de enfermería de la Empresa Social del Estado Hospital Sandiego de Cereté, 2023 (2023)
The objective of this research was to evaluate the level of work stress perceived by nursing professionals and auxiliaries of the E.S.E. Hospital Sandiego de Cereté, Córdoba in 2023. The data collection technique used was the survey, likewise the instrument was the questionnaire for the evaluation of stress included in the battery of instruments for the evaluation of psychosocial risk factors which has been designed to evaluate symptoms of stress, distributed in four categories: physiological, social behavior, psychoemotional and intellectual and work. The type of study is descriptive, cross-sectional with a quantitative approach, likewise the type of sampling is non-probabilistic at convenience, the sample was made up of 45 professionals and nursing assistants active in the study scenario who voluntarily were part of the research, where 88.9% of the population are women and 11.1% men. The findings indicate that nursing professionals, as well as auxiliaries, are at a medium risk level of stress by obtaining a transformed score of 16.3, with a difference of 2.2 points above the 14.1 of auxiliaries. Keywords: Work stress, job satisfaction